Stenoloba ronkayi Sohn & Tzuoo 2012—a new homonym of S. ronkayi Behounek & Kononenko, 2010 and new synonym of S. glauca Kononenko & Ronkay 2001. A postscript to the revision of Chinese Stenoloba (Lepidoptera, Noctuidae) - Han, H. L.; Kononenko, V. S. (Zootaxa, 2015)
Stenoloba Staudinger, 1892 is an exclusively East Asian Noctuidae genus of the subfamily Bryophilinae. After global revision of the genus (Kononenko & Ronkay 2000, 2001) the numerous regional revisions and descriptions of separate species appeared (Ronkay 2001; Han & Lu 2007; Han & Kononenko 2009; Behounek & Kononenko 2010; Han et al. 2011; Pekarsky 2011; Sohn & Tzuoo 2012; Pekarsky et al. 2013; Pekarsky & Saldaitis 2013).